The relationship between socioeconomic status and risky drinking in Denmark: a cross-sectional general population study - Abdu Kedir Seid (BMC Public Health, 2018)
Abstract Background Socioeconomic status (SES) is regarded as consisting of education, income and employment. However, the relationship of these three components to alcohol use behaviours, such as risky single occasion drinking (RSOD) is unclear. The aim of the present paper is to specify how the three SES components relate to RSOD in a cross-sectional survey sample of the Danish general population. Method Data from a 2011 Danish national representative survey (n = 3600) was analysed by multiple logistic regression to assess the influence of three dimensions of individual SES (education, income, employment) on RSOD. Results Components of SES were not found to be significantly associated with RSOD independently nor in combination. Conclusion In the Danish context, SES was not associated with RSOD.